Controle da coccidiose, desempenho e qualidade de carcaça de cordeiros alimentados com dietas contendo óleos funcionais - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The intensive use of anthelmintic and coccidiostats in order to reduce the impacts caused by gastrointestinal parasites in sheep has led to concerns about parasitic resistance. In addition, there is a demand from consumers for healthier food, free of residues. In addition, there is a demand from consumers for healthier food, free of residues. Therefore, this has led researchers to look for new alternatives as possible substitutes for chemical treatments. The study aimed to evaluate the inclusion of functional oil in the diet of confined lambs as a possible substitute for sodium monensin in the control of coccidiosis, as well as its effect on performance and carcass characteristics. For parasitological and performance evaluation, 34 lambs were used, distributed in three groups: functional oil (OF) (n = 12); control (CONT) (n = 12) and sodium monensin (MON) (n = 10). However, for histological and carcass characteristics evaluations, only 14 animals were evaluated (five from the OF group, four from CONT and five from MON). Egg counts per gram of feces (OPG) and oocysts per gram of feces (oOPG) were performed. As well as, blood samples to determine globular volume (VG), total plasma protein (PPT), albumin, globulin, eosinophil and leukocyte. Hot carcass weight (PCQ), hot carcass yield (RCQ), carcass and leg compactness index were determined. The yields of the cuts were also performed, the dimensions of the Longissimus dorsi muscle and the proximate composition of the 12th rib. Stool, blood and weighing samples were performed on days 0, 14, 28, 41 and 55 days of the experiment. There was a difference in the egg count per gram of oocyst feces (oOPG) on day 14. On this day, the OF showed a higher count when compared to the others (P<0.05). On the 28th, this same group had the highest oOPG count for the entire experimental period (827 ± 267 oOPG). For body weight on day 28, 41 and 55 the animals that received OF had the lowest weight, 19.75 ± 2.50, 23.77 ± 2.48 and 27.05 ± 3.06, respectively. The different treatments did not alter the values of globular volume, total plasma protein and globulin. The eosinophil count (9.02 ± 0.66) and leukocyte (8991 ± 0.18) was lower for the MON group. In the intestine samples, all groups presented an epithelium shedding, crypt hyperplasia and goblet cells, indicating a marked inflammatory process. The slaughter weight showed no difference (P>0.05) between treatments, as well as the data regarding carcass characteristics. The consumption of dry matter was similar between groups (P>0.05). The cut yield was not influenced by the inclusion of OF or MON. The dimensions of the Longissimus dorsi muscle were the same for all groups. Regarding the proportion (%) of bone, muscle and fat, the animals that received OF presented a higher proportion of muscle (P<0.05). During the study it was possible to observe that the MON group was more effective in controlling coccidiosis when compared to the OF group. The high prevalence of oOPG (P<0.05) in OF reduced the animals' performance. Regarding carcass characteristics, the absence of the influence of additives may be related to the diet offered, which possibly standardized the carcass finish. Studies with functional oils are still inconsistent in the literature and more work in vivo needs to be carried out to understand its effect.
Keywords: aditivos; extrato de planta; ovinocultura; parasitas; adittive; plant extract; parasites; sheep farming; CNPQ::CIENCIAS AGRARIAS::ZOOTECNIA